The Feasibility of Supplementing Shisha Research Based Teaching Material on Circulatory System Materials to Improve High School Students Concept Understanding - Alma, Wildha; Lisdiana, Lisdiana (FMIPA UNNES, 2022)
Teaching material supplements were developed based on an analysis of students' needs in the use of learning resources used in everyday life. In the process of learning biology, understanding the concept is very important to be mastered by students. Concept understanding helps students remember the lessons they have learned over a long period of time. This study aims to determine the feasibility of teaching material supplements in biology learning. This research is a Research and Development study which refers to the steps (1) potential and problems; (2) data collection; (3) product design; (4) design validation; (5) design revision; (6) product testing; (7) product revision; (8) final production. The parameters of the feasibility of teaching material supplements are seen from the material validation, media validation, teacher responses, student responses and concept understanding tests. The results of the study obtained data that the validity of the material showed a score of 83.7% with very valid criteria, the validity of the media showed a score of 95.1% with very valid criteria, the responses of students' responses showed 82.625% results with very feasible criteria, the teacher's response showed 86.6% results with very feasible criteria. as well as classical completeness of the concept understanding test reached 91.17% provided that students achieved a mastery score of â‰¥ 70 and an average n-gain of 0.55 in the moderate category. The conclusion of this research is that shisha research-based teaching material supplements are suitable for use as learning materials on the circulatory system.